Upgrading Silica/Glass Sand Concentrate Applying Cationic Flotation - BAYAT, OKTAY; VAPUR, HUSEYIN; I. ARSLAN, VOLKAN (Asian Journal of Chemistry, 2010)
In this study, upgrading of flotation silica/glass sand concentrate (clear flat glass quality), sized 0.600 ± 0.106 mm, from Camis Mining Company (Mersin, Turkey) was investigated applying amine flotation. In the experimental work; Armac-C, Armac-T, Armoflote-64, Armoflote-586, Armoflote-565 and Armoflote-P were used as cationic collectors keeping other flotation conditions constant. Armoflote-565 gave the best results as an effective collector since the Fe2O3 content was reduced from 0.098-0.03 % with 70.4 % iron removal efficiency after applying two cleaning stages of amine (Armoflote-565, 800 g/t) flotation onto the glass sand concentrate (clear flat glass quality) treated traditionally in the plant. The upgraded silica concentrate can be utilized as for manufacturing the household white glass (Fe2O3 ≤ 0.05 %). The floated product (the tailings of the amine flotation) can be a raw material for production of some titanium concentrates due to its TiO2 content.